Data Don’t Lie: A Comparative Study of Nepal’s Development under Absolute Monarchy and Post-Monarchy Democratic Era - Yadav, Manoj Kumar; Basyal, Devid Kumar; Bhusal, Indra Prasad; Anderson, Chad David (Economic Journal of Development Issues, 2024)
Correction: On 24/04/2025, the updated PDF was loaded because it was found that some of the figures were inadvertently repeated and misplaced. A widespread perception among the Nepalese people is that Nepal was in a better position in terms of development during the party-less Panchayat political system under the absolute monarchy from 1960 to 1990 than in the post-Panchayat democratic period after 1990. This article presents a comparative study of major development indexes during the Panchayat and post-Panchayat periods and aims to clarify the origins and reality of this perception. Data were obtained and analyzed using secondary global sources such as UNICEF, UNFPA, UNESCO, Education Statistics, World Bank, etc. Further comparison is made with corresponding Indian indexes for a better assessment of development after the emergence of globalization. The comparison shows that, contrary to the common perception, Nepal is in a much better development position in most of the indexes in the post-Panchayat democratic period.